Edge‐hydroxylated Boron Nitride for Oxidative Dehydrogenation of Propane to Propylene. Issue 10 (12th May 2017) - Shi, Lei; Wang, Dongqi; Song, Wei; Shao, Dan; Zhang, Wei‐Ping; Lu, An‐Hui
Abstract: The front cover artwork for Issue 10/2017 is provided by the Advanced Energy Materials and Catalysis Research Group, Dalian University of Technology and the Institute of High Energy Physics, Chinese Academy of Sciences. The image shows that a metal‐free catalyst, edge hydroxylated boron nitride, can efficiently catalyze the oxidative dehydrogenation of propane to propylene with superior selectivity and negligible CO2 emission. See the Full Paper itself athttps://doi.org/10.1002/cctc.201700004 . Abstract : "Edge‐hydroxylated boron nitride shows superior selectivity for the oxidative dehydrogenation of propane to propylene with only negligible CO2 formation" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201700004 .